Effects of Cane Use and Position on Performance of the Sit-to-Stand Task in Stroke Patients. (July 2018) - Li, Tung-Chou; Tu, Keng-Hua; Shiue, Huei-Sheng; Lin, Mau-Roung
Abstract : Objective: The aim of the study was to examine the effect of cane use and cane positions on the sit-to-stand performance of stroke patients. Design: In a crossover study, 30 stroke patients performed sit-to-stand test in seven situations in a random sequence: without a cane, three positions with a regular cane (parallel to the ankle, parallel to the 5th toe, and 10 cm in front of the 5th toe), and the same three positions with a quad cane. The peak vertical ground reaction force and maximum vertical cane support force during sit-to-stand were recorded. Results: Using a cane significantly reduced the peak ground reaction force by 3% to 9% of body weight compared with that without a cane ( P = 0.000–0.023). Different cane positions strongly influenced the maximum cane support force and peak ground reaction force. When the cane was closer to the ankle, the maximal cane support force increased by 6.7% to 8.6% of body weight, which resulted in a decrease in the peak ground reaction force. Conclusions: Both types of cane reduced lower limbs' load during sit to stand. When the cane was closer to the trunk, the load on legs was lessened, whereas the load on the upper limb increased. Upper limb's load during sit to stand was greater when using quad cane than using regular cane.